Improving the therapeutic efficacy of gene therapy for duchenne muscular dystrophy (DMD) by evaluating and managing inflammation - Raghavan, Kadalraja; Ikewaki, Nobunao; Preethy, Senthilkumar; Abraham, Samuel J. K. (Frontiers in Genetics, 2025)
Duchenne muscular dystrophy (DMD): is a rare, life-limiting genetic disorder for which no curative treatment currently exists. While various gene therapy approaches, some approved and others still under clinical investigation have been explored, they have not consistently produced the desired outcome and, in some cases, have been associated with serious adverse effects, including mortality. A critical factor we wish to highlight is the hostile inflammatory environment inherent to skeletal muscles’ pathology in DMD, which may be further aggravated by gene therapy, either due to the viral vector used or the gene component itself. Therefore, a comparative and detailed evaluation of inflammatory biomarkers between control and treatment arms in such clinical trials is essential to determine whether therapeutic benefits are being compromised by inflammation. Based on the implications of such hostile environment on the therapeutic outcome, adding a safer and efficacious management strategy to mitigate the inflammation during gene therapies is considered indispensable. Therefore, we recommend further research on adjuvant anti-inflammatory approaches to ensure safety and improvement of the therapeutic outcome of gene therapies for DMD.